Strategies to manage hepatitis C virus (HCV) disease burden. (May 2014) - Wedemeyer, H.; Duberg, A. S.; Buti, M.; Rosenberg, W. M.; Frankova, S.; Esmat, G.; Örmeci, N.; Van Vlierberghe, H.; Gschwantler, M.; Akarca, U.; Aleman, S.; Balık, İ.; et al.
Summary: The number of hepatitis C virus (HCV) infections is projected to decline while those with advanced liver disease will increase. A modeling approach was used to forecast two treatment scenarios: (i) the impact of increased treatment efficacy while keeping the number of treated patients constant and (ii) increasing efficacy and treatment rate. This analysis suggests that successful diagnosis and treatment of a small proportion of patients can contribute significantly to the reduction of disease burden in the countries studied. The largest reduction in HCV‐related morbidity and mortality occurs when increased treatment is combined with higher efficacy therapies, generally in combination with increased diagnosis. With a treatment rate of approximately 10%, this analysis suggests it is possible to achieve elimination of HCV (defined as a >90% decline in total infections by 2030). However, for most countries presented, this will require a 3–5 fold increase in diagnosis and/or treatment. Thus, building the public health and clinical provider capacity for improved diagnosis and treatment will be critical.